Poirot. Series 13 [videorecording (DVD)] - Strickland, John (Television director); Lydon, Peter; Suchet, David; Fraser, Hugh; Wanamaker, Zoë, 1949-; Christie, Agatha, 1890-1976; Christie, Agatha, 1890-1976; Christie, Agatha, 1890-1976; Christie, Agatha, 1890-1976; Christie, Agatha, 1890-1976 (Acorn Media, 2014)
Belgian detective Hercule Poirot investigates a variety of mysteries.